Anxiogenic and antinociceptive effects induced by corticotropin-releasing factor (CRF) injections into the periaqueductal gray are modulated by CRF1 receptor in mice - Miguel, Tarciso Tadeu [UNESP]; Nunes-de-Souza, Ricardo Luiz [UNESP] (Academic Press Inc. Elsevier B.V., 2011)
Chemical or electrical stimulation of the dorsal portion of the midbrain periaqueductal gray (dPAG) produces anxiogenic and antinociceptive effects. In rats, chemical stimulation of dPAG by local infusion of the neuropeptide corticotropin-releasing factor (CRF) provokes anxiogenic effects in the elevated plus-maze test (EPM). CRF also produces antinociception when injected intracerebroventricularly in rats, however it remains unclear whether this response is also observed following CRF injection into the dPAG in mice. Yet, given that there are CRF1 and CRF2 receptor subtypes within the PAG, it is important to show in which receptor subtypes CRF exert its anxiogenic and antinociceptive effects in the dPAG. Here, we investigated the role of these receptors in the anxiogenic (assessed in the EPM) and antinociceptive (assessed by the Formalin test: 2.5% formalin injection into the right hind paw) effects following intra-dPAG infusion of CRF in mice. The results show that intra-dPAG injections of CRF (75 pmol/0.1 mu l and 150 pmol/0.2 mu l) produced dose-dependent anxiogenic and antinociceptive effects. In addition, local infusion of NBI 27914 (5-chloro-4-(N-(cyclopropyl) methyl-N-propylamino)-2-methyl-6-(2,4,6-trichlorophenyl)-aminopyridine; 2 nmo1/0.2 pl), a CRF1 receptor antagonist, completely blocked both the anxiogenic and antinociceptive effects induced by local infusion of CRF, while that of antisauvagine 30 (ASV30; 1 nmol/0.2 mu l), a CRF2 receptor antagonist, did not alter the CRF effects. Present results are suggestive that CRF1 (but not CRF2) receptors play a crucial role in the anxiogenic and antinociceptive effects induced by CRF in the dPAG in mice. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anxiety; Antinociception; CRF1 and CRF2 receptors; Periaqueductal gray; Elevated plus-maze; Mice